2019
DOI: 10.1002/em.22345
|View full text |Cite
|
Sign up to set email alerts
|

4‐nitrophenol exposure in T24 human bladder cancer cells promotes proliferation, motilities, and epithelial‐to‐mesenchymal transition

Abstract: Although health hazards of 4‐nitrophenol (PNP) exposure have been reported, the adverse effects of PNP exposure on cancer biological features are still unknown. We investigated the effects of administration of PNP in T24 human bladder cancer cells. The results showed that PNP exposure promoted cellular proliferation, migration and invasion, inhibited adhesion and apoptosis in vitro. Using quantitative real‐time PCR, we found that (1) the mRNA expression levels of cell‐cycle regulators PCNA, cyclin D1 and COX‐2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…PPAR-γ ligands are expected to become promising therapeutic agents for chemoprevention and treatment. However, previous studies on PPAR-γ activation using several agonists have not provided consistent findings, such as the tumor suppressive or oncogenic role of PPAR-γ, in a heterogeneous nature in bladder cancer ( 9 , 10 ). Furthermore, limited information is currently available on the expression of PPAR-γ in carcinoma in situ (CIS), such as flat carcinoma.…”
Section: Introductionmentioning
confidence: 91%
“…PPAR-γ ligands are expected to become promising therapeutic agents for chemoprevention and treatment. However, previous studies on PPAR-γ activation using several agonists have not provided consistent findings, such as the tumor suppressive or oncogenic role of PPAR-γ, in a heterogeneous nature in bladder cancer ( 9 , 10 ). Furthermore, limited information is currently available on the expression of PPAR-γ in carcinoma in situ (CIS), such as flat carcinoma.…”
Section: Introductionmentioning
confidence: 91%
“…Metabolic-wise, researchers have found that the activation of PPAR-g could improve glucose and lipid metabolism, proving for the high demand of energy in the proliferation, migration and invasion of human prostate cancer cells and mice model (52). Interestingly, regarding factors involved in cell cycle, another study has found that the pro-apoptotic genes c-Myc and Bax are inhibited while cell-cycle regulators PCNA, cyclin D1 and COX-2 are promoted along with PPAR-g activation (40,55). In several studies, with the cell culture of human renal cell carcinoma, human prostate cancer xenografts in nude mice, as well as brain cancer in vivo, the increased expression of PPAR-g are all prognostically negative and pro-metastatic (56)(57)(58).…”
Section: Promotion Of Tumorigenesismentioning
confidence: 99%
“…Through chronic sublethal exposure, methomyl is also a strong genotoxic agent that induces DNA damage and cytotoxicity 38 . Likewise, PNP is an endocrine disruptor that has oncogenic potential 39 . PNP has been reported to exert hepatotoxic effects in rodents by increasing liver transcription levels of genes encoding the estrogen receptor-α, glutathione S-transferase, and www.nature.com/scientificreports/ aryl hydrocarbon receptor signaling pathway 40 .…”
Section: Discussionmentioning
confidence: 99%